2004
DOI: 10.1074/jbc.m407340200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T Isoforms Affect the Ca2+ Sensitivity of Force Development in the Presence of Slow Skeletal Troponin I

Abstract: In this study we investigated the physiological role of the cardiac troponin T (cTnT) isoforms in the presence of human slow skeletal troponin I (ssTnI). ssTnI is the main troponin I isoform in the fetal human heart. In reconstituted fibers containing the cTnT isoforms in the presence of ssTnI, cTnT1-containing fibers showed increased Ca 2؉ sensitivity of force development compared with cTnT3-and cTnT4-containing fibers. The maximal force in reconstituted skinned fibers was significantly greater for the cTnT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 53 publications
6
68
2
Order By: Relevance
“…Although the molecular mechanism of cooperativity is still not clearly understood, the Ca 2ϩ dependence of muscle contraction is known to be highly cooperative with Hill coefficients in cardiac fibers ranging from one to three depending on the system used (21,30,31). The cTnI R145G HCM mutation was previously shown to cause a decrease in the Hill coefficient when compared with wild-type cTnI (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism of cooperativity is still not clearly understood, the Ca 2ϩ dependence of muscle contraction is known to be highly cooperative with Hill coefficients in cardiac fibers ranging from one to three depending on the system used (21,30,31). The cTnI R145G HCM mutation was previously shown to cause a decrease in the Hill coefficient when compared with wild-type cTnI (14).…”
Section: Discussionmentioning
confidence: 99%
“…TnC, TnI, and TnT were purified as described previously (15,16). Rabbit skeletal actin and bovine ventricular cardiac tropomyosin (Tm) were purified from acetone powders as described previously (34,35).…”
Section: Methodsmentioning
confidence: 99%
“…Different isoforms of the troponin complex (Tn) within an organism and between different species help to tune the response of TnC to Ca 2ϩ to meet developmental and environmental demands of the heart (11)(12)(13)(14)(15). In this regard, TnC does not behave like a simple switch because the Ca 2ϩ binding properties of the regulatory EF-hand of TnC are modulated by interactions with its protein binding partner, troponin I (TnI) (16,17).…”
mentioning
confidence: 99%
“…There is nearly as strong a correlation between the summed relative abundance of the same two transcripts and the power output of intact muscle (Figure 3d). Experiments in other animals have repeatedly shown that manipulation of Tnt genes and/or protein isoforms affects muscle calcium sensitivity and contractile performance (Ogut et al, 1999;Gomes et al, 2002Gomes et al, , 2004MacFarland et al, 2002;Nassar et al, 2005;Brotto et al, 2006;Chandra et al, 2006), and single amino-acid replacement mutations in human Tnt also have these effects (Hernandez et al, 2005).…”
Section: As and The Generation Of Plastic Organism-level Phenotypesmentioning
confidence: 99%